Role of mathematics in the study plans of faculty of technology at VDU - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2021)
The object of the paper is to investigate what number of hours was dedicated for mathematics in 1922–1943. The program of mathematics lectured to students of the Faculty of Technology since 1930 is analyzed.